Characterization of Prejunctional Muscarinic Receptors: Effects on the Release of VIP and Functional Responses and Receptor Expression in the Ovine Submandibular Gland - Ryberg, Anders T. (Hindawi Publishing Corporation, 2009)
In the in vivo experiments on anaesthetized sheep, it was presently examined whether muscarinic receptor antagonists with diverse selectivity affect the release of VIP in response to electrical stimulation of the parasympathetic chorda tympanic nerve differently, and if the changes in the release could be associated to altered secretory and vasodilator responses. The location of the muscarinic receptor subtypes was examined also. In the experiments, blood was collected out of the submandibular venous drainage before and during electrical stimulation of chorda tympani nerve in the absence and presence either of pirenzepine or methoctramine. While metchoctramine increased the output of protein, pirenzepine inhibited flow of saliva and increased protein output, vasodilatation, and VIP output. In morphological examinations, the inhibitory muscarinic M4 receptor occurred interacinarily in the gland. It is concluded that prejunctional muscarinic receptors, most likely of the M4 subtype, exert inhibitory modulation of the parasympathetic release of VIP in the ovine submandibular gland.